Iranian cosmopolitanism : a cinematic history - Rekabtalaei, Golbarg, 1983- (Cambridge University Press, 2018)
From popular and 'New Wave' pre-revolutionary films of Fereydoon Goleh and Abbas Kiarostami to post-revolutionary films of Mohsen Makhmalbaf, the Iranian cinema has produced a range of films and directors that have garnered international fame and earned a global following. Golbarg Rekabtalaei takes a unique look at Iranian cosmopolitanism and how it transformed in the Iranian imagination through the cinematic lens. By examining the development of Iranian cinema from the early twentieth century to the revolution, Rekabtalaei locates discussions of modernity in Iranian cinema as rooted within local experiences, rather than being primarily concerned with Western ideals or industrialisation. Her research further illustrates how the ethnic, linguistic, and religious diversity of Iran's citizenry shaped a heterogeneous culture and a cosmopolitan cinema that was part and parcel of Iran's experience of modernity. In turn, this cosmopolitanism fed into an assertion of sovereignty and national identity in a modernising Iran in the decades leading up to the revolution.
Keywords: Cosmopolitanism in motion pictures.; Motion pictures -- Iran -- History -- 20th century.; Motion picture industry -- Iran -- History -- 20th century.; Cosmopolitisme au cinéma.; Cinéma -- Iran -- Histoire -- 20e siècle.; Cinéma -- Industrie -- Iran -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference.; Cosmopolitanism in motion pictures; Motion picture industry; Motion pictures; Iran; 1900-1999; History